Structure guided generation of thieno[3, 2-d]pyrimidin-4-amine Mycobacterium tuberculosis bd oxidase inhibitors. Issue 1 (12th January 2021) - Hopfner, Sarah M.; Lee, Bei Shi; Kalia, Nitin P.; Miller, Marvin J.; Pethe, Kevin; Moraski, Garrett C.
Abstract : Screening for inhibitors of Cyt- bd in Mycobacterium bovis BCG and Mycobacterium tuberculosis revealed thieno[3, 2- d ]pyrimidine (7 ) which through SAR efforts resulted in an improved analogue (19 ) of this scaffold. Abstract : Cytochrome bd oxidase (Cyt- bd ) is an attractive drug target in Mycobacterium tuberculosis, especially in the context of developing a drug combination targeting energy metabolism. However, currently few synthetically assessable scaffolds target Cyt- bd . Herein, we report that thieno[3, 2- d ]pyrimidin-4-amines inhibit Cyt- bd, and report an initial structure–activity-relationship (SAR) of 13 compounds in three mycobacterial strains: Mycobacterium bovis BCG, Mycobacterium tuberculosis H37Rv and Mycobacterium tuberculosis clinical isolate N0145 in an established ATP depletion assay with or without the cytochrome bcc  :  aa 3 (QcrB) inhibitor Q203. All compounds displayed activity against M. bovis BCG and the M. tuberculosis clinical isolate strain N0145 with ATP IC50 values from 6 to 54 μM in the presence of Q203 only, as expected from a Cyt- bd inhibitor. All derivatives were much less potent against M. tuberculosis H37Rv compared to N0145 (IC50 's from 24 to >100 μM and 9–52 μM, respectively), an observation that may be attributed to the higher expression of the Cyt- bd -encoding genes in the laboratory-adapted M. tuberculosis H37Rv strain. N -(4-( tert -butyl)phenethyl)thieno[3, 2- d ]pyrimidin-4-amine (19 ) was the most active compound with ATP IC50 values from 6 to 18 μM against all strains in the presence of Q203, making it a good chemical probe for interrogation the function of the mycobacterial Cyt- bd under various physiological conditions.